Optimized production of Omega-3 AND Omega-6 fatty acids from Chlorococcum novae-angliae - Çalışkan, Elifcan. (Thesis (M.S.)-Bogazici University. Institute of Environmental Sciences, 2019., 2019)
Essential fatty acids (ω-3 and ω-6) are key examples of highly demanded nutraceutical supplements as they are substantially required for the development of nervous system and brain in children, and to maintain a healthy cardiovascular system in adults. Major sources of essential fatty acids in nature are fungi, plant, fish, and microalgae. Among them, microalgae feedstocks have gained significant attention recently as they grow much faster and provide higher biomass productivity compared to plant species or fungi. Moreover, microalgae are primary producers of essential fatty acids. Although there are many alternatives for ω-3 and ω-6 fatty acids in the international market which are mainly fish oil-based, pollution of water resources, accumulation of heavy metals, organic contaminants, dioxin in fish bodies, undesirable odor of fish oils, and reduced fish stocks due to overfishing became major concerns for sustainability of these resources. Therefore, microalgae based ω-3 and ω-6 fatty acids are more desirable in the market as they appeal more to vegans and vegetarians due to their plant-based nature. In this study, Chlorococcum novae-angliae, a green microalgae that natively synthesize high amounts of ω-3 and ω-6 fatty acids has been exposed to various growth conditions (light, nitrogen, salinity, and temperature stress) to optimize their growth conditions for maximal production of ω-3 and ω-6 fatty acids as a potential candidate for achieving large-scale production goals. For this reason, lipid content and fatty acid profiles of Chlorococcum novae-angliae were investigated in order to find out biosynthesis levels of ω-3 and ω-6 fatty acids.
Keywords: Fatty acids.; Omega-3 fatty acids.; Omega-6 fatty acids.